Pengaruh Flash Sale dan Tagline “Gratis Ongkir” terhadap Pembelian Impulsif melalui Variabel Intervening Emosi Positif pada Marketplace di Kota Palembang - Al Fajri, M Adrian; Moelyati, Trisniarty Adjeng; Yamalay, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This research aims to determine the influence of Flash This research aims to determine the influence of Flash Sale and Free Shipping Tagline on Impulsive Purchases through the Intervening Variable of Positive Emotions on Marketplace in Palembang. The sample was drawn using the Hair formula, with a sample size of 150 Marketplace consumers in Palembang City. The required data is primary data obtained from the distribution of questionnaires to Marketplace consumers in Palembang. The analysis technique used in this study is the Structural Equation Model (SEM) analysis technique. The results of the SEM analysis technique show that firstly, there is a positive and significant influence between the Flash Sale variable and the Impulsive Purchase variable. Secondly, there is a positive and significant influence between the Free Shipping Tagline variable and the Impulsive Purchase variable. Thirdly, there is a positive and significant influence between the Flash Sale variable and the Positive Emotions variable. Fourthly, there is a positive and significant influence between the Free Shipping Tagline variable and the Positive Emotions variable. Fifthly, there is a positive and significant influence between the Positive Emotions variable and the Impulsive Purchase variable. Sixthly, there is a positive and significant influence between the Flash Sale variable and the Impulsive Purchase variable through the intervening variable of Positive Emotions. And seventh, there is a positive and significant influence between the Free Shipping Tagline variable and the Impulsive Purchase variable through the intervening variable of Positive Emotions.